Pulmonary hemorrhage associated with severe leptospirosis – the role of low dose intravenous methylprednisolone - Lim, Christopher Thiam Seong; Tan, Yi Jun; Then, Ru Fah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Leptospirosis has a wide range of presentation which ranges from mild flu-like symptoms, to severe form including renal failure, liver failure, and hemorrhage. Pulmonary involvement can progress from subtle clinical features to life threatening pulmonary hemorrhage and acute respiratory distress syndrome. Although benefits of corticosteroids in adult respiratory distress syndrome have been proven and accepted, evidence for use of corticosteroids in pulmonary leptospirosis is still limited. Given the vasculitic nature of severe leptospirosis, it has been proposed that addition of intravenous corticosteroid therapy, particularly in cases of pulmonary involvement is beneficial. We report a case of leptospirosis with suspected pulmonary hemorrhage which deteriorates after a few days of admission in our tertiary hospital. We have demonstrated that the prescription of a lower dose of corticosteroid than what was widely reported in the literature can equally led to a satisfactory recovery of the pulmonary hemorrhage.